Kontribusi Keharmonisan Keluarga Dan Kedisiplinan Belajar Siswa Terhadap Hasil Belajar Matematika Pada Siswa Kelas X Sman 2 Klaten Tahun Ajaran 2015/2016 - Ri'ayati, Dewanti; , Idris Harta, M.A.,Ph.D; , Sri Rejeki M.Pd, M.Sc (2017)
Dewanti Ri 'Ayati. A410122007. "THE CONTRIBUTIONS OF FAMILY HARMONY STUDENTS DISCIPLINE LEARNING ON MATHEMATTICS LEARNING OUTCOMES IN GRADE X SENIOR HIGH SCHOOL 2 KLATEN YEAR 2015/2016". Thesis. The Faculty of Education Univesity of Muahammadiyah Surakarta. December 2016. The aim of this study is to examine the extent to which: 1) the contribution of family harmony on students mathematics leaning outcomes; 2) the contribution of the discipline in learning on students mathematics learning outcomes; and 3) the contribution of family harmony and discipline in learning mathematics together on students mathematics learning outcomes. This is a correlative quantitative research. The population in this study were all students majoring in science in grade X SMAN 2 Klaten year 2015/2016 amounted to 240 students and the sample was 70 students chosen by proportional systematic random sampling. The data analysis in this study using multiple linear regression. The results showed that: 1) Family harmony on students mathematics learning outcomes, it can be seen from the partial test results that tvalue = 3,758 > ttable 2,000; 2) discipline in learning on students the mathematics learning outcomes , it can be seen from the partial test results that tvalue = 2,331 > ttable 2,000; and 3) family harmony and discipline in learning mathematics together on students mathematics learning outcomes, it can be seen from the results of simultaneous test is Fvalue 35.681> Ftable = 3.130.